SIKAP POLITIK ANGGOTA DPR PERIODE 1999-2004 DALAM PROSES PEMBENTUKAN UNDANG-UNDANG (Studi Analisis Isi Proses Pembentukan Undang-Undang Nomor 20 Tahun 2002 Tentang Ketenagalistrikan) - ERWANSYAH SJARIEF (JURNAL MITRA MANAJEMEN, 2013)
ABSTRACTThe law Number 20 of the Year 2002 on Electric Power is considered problematic by manyin a number of ways. The political attitude of the members of parliament (MPs) who whereinvolved in the making of the law may be suspected to have played a part in the adversesituation. This content analysis and documentary study reported here aimed to assess theunderstanding of the MPs of the 1999-2004 period about the substance of the electric powerlaw, the attitude they demonstrated in the making of the law, and their understanding ofethical principle underlying good governance required in the construction of laws. Data werecollected through document analysis, observation, and in-depth interviews. Results revealeda number of attitude demonstrated by the members of parliament when constructing the lawthat indicated law-level understanding of the substance of the law and also weak complianceto ethical principle.Keywords: political attitude, power, opportunistic behavior, political animal, money politics,liberalism, favorable, bounded rationality